Overview of the Regulation of Health Claims in Japan - Yokotani, Kaori (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
According to the international guidelines of the Joint FAO/WHO Food Standards Program, CodexAlimentarius Commission, individual countries create health claims for foods. These health claims areregulated by government regulatory agencies such as the Food and Drug Administration (FDA) in the USAand the European Food Safety Authority (EFSA) in the European Union. In Japan, the Ministry of Health,Labor, and Welfare (MHLW) created âFood for Specified Health Uses (FoSHU)â in 1991 and âFood withNutrient Function Claims (FNFC)â in 2001. Thereafter, rules similar to those in Japan have been createdelsewhere in the world. Currently, the system is regulated and updated by the Food Safety Committee, theConsumer Affairs Agency, and the Consumer Committee. Special foods attached with health claims inJapan are categorized into the following two groups according to their functions for health, their users, andpurposes: (1) Food for Special Dietary Uses (FOSDU) and (2) Food with Health Claims (FHC). FoSHU iscategorized as both FOSDU and FHC. Scientific evidence of the claims and the safety are confirmed withthe finished product by the government agency, and then the special label is used on these foods (Fig. 1).The FoSHU system was established 25 years ago and health problems have not occurred because of using it.This is because there are many scientific evidences about FoSHUâs efficacy and safety. However, healthfoods used in Japan are mostly just so-called health foods, and the safety is not confirmed by the Japanesegovernment. Furthermore, safety evaluations of these products are only general and specific toxicity studies,because these are just foods. The targets of health foods are not patients, but a previous study indicated thatmost patients used dietary supplements without consulting their physicians. If patients take medicines alongwith it, health problems such as food-drug interactions may occur. For medicines, not only general andspecific toxicity studies but also pharmacokinetics studies are performed. Over 80% of drug-metabolizingreactions are oxidation reactions by cytochrome P450s (CYP), and drug interactions naturally occur viaCYPs induction or inhibition. Generally, CYPs induction decreases drug efficacy, and CYPs inhibitionincreases drug efficacy. In health food-drug interactions as well, these reactions occur via CYPs. Finally, Idiscuss my recent studies on the safety of herbal extracts such as herb-drug interactions via inductions ofhepatic drug-metabolizing enzymes.Keywords: health food, health claim, regulation